Phycoremediation of textile wastewater by unicellular microalga Chlorella pyrenoidosa - Pathak, V. V.; Singh, D. P.; Kothari, R.; Chopra, A. K. (Cellular and Molecular Biology, 2014)
The potential application of microalga Chlorella pyrenoidosa was investigated for phycoremediation of textile wastewater. Two 15 days batch experiment containing autoclaved and unautoclaved textile wastewater were performed to measure the efficiency of alga to remediate the wastewater. Experiments were set at equivalent external conditions and pollutant load was measured on alternate of 5 days to determine the pollutant removal efficiency of alga. Alga was found to be more efficient in removal of pollutants load in autoclaved wastewater; agents of eutrophication such as nitrate and phosphate are reduced by 62% ±0.5 and 87% ±0.7 respectively while organic load in terms of BOD is reduced by 81% ±0.2 whereas, In unautoclaved wastewater in presence of algal-bacterial consortium, nitrate and phosphate were removed by 81% ±1 and 36% ±2.2 while BOD is reduced by 73% ±1.6 only. Another time dependent experiment of dye removal was also performed to measure the adsorption potential of selected dried algal biomass. An equal amount of dried algal biomass was introduced to various range of textile wastewater simulated with methylene blue (MB) dye. The maximum colour removal was observed afterduration of 30 minutes by dry algal biomass.